A Drug-Induced Acute Pancreatitis Retrospective Study - Ann-Lorie Gagnon; Alexandre Lavoie; Marie-Pier Frigon; Alban Michaud-Herbst; Karine Tremblay (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. Drugs are considered a relatively rare and understudied cause of acute pancreatitis (AP). The lack of convincing and conclusive data on drug-induced AP (DIAP) complicates the diagnosis as well as the identification of the causative drug. The aim of this study is to document causes of DIAP cases that occurred in the Saguenay-Lac-Saint-Jean (SLSJ) population. Methods. We have conducted a retrospective and descriptive population-based study of DIAP cases that occurred between 2006 and 2014 in the six hospitals serving the entire SLSJ population. Cases were selected from the Quebec Ministry of Health hospitalizations registry (MED-ECHO) administrative public database. A medical chart review was performed in an attempt to characterize DIAP hospitalizations and to identify the imputable drugs. Results. During the studied period, 75 cases (30.7% male, 69.3% female) were included totaling 90 hospitalizations for DIAP. Among them, 50 causative drugs were identified and were distributed in 17 different drug classes. Recurrent DIAPs were documented in 13 cases, and among them, 6 cases have experimented a positive rechallenge. Six drugs (5-fluorouracil, atorvastatin, bortezomib, nilotinib, rosuvastatin, and triamcinolone) were associated with the highest degree of evidence. The most common causative drugs of DIAP hospitalization were azathioprine (n = 7), followed by atorvastatin (n = 6), hydrochlorothiazide (n = 5), rosuvastatin (n = 4), and codeine (n = 4). Conclusions. This study has added new evidences about potentially pancreatitis-associated drugs in literature. This is the first study to report definite 5-fluorouracil- and triamcinolone-induced AP. An updated version of the evidence-based literature review is needed to support the clinicians in the identification of the causative drugs.